Shocks, hazard risk management and resilience from an institutional outlook: What lessons for a (smart) city? - Ramona Țigănașu; Alina Nicuță (CES Working Papers, 2021)
As a result of various shocks and natural disasters, the scientific community has expressed a particular interest in the study of countries resilience capacity, after being affected by a hazard. In association with this concern, hazard risk management is becoming a relevant and highly debated topic, due to an increased exposure of people to devastating disasters, all around the world. In the context of fighting for the mitigation of threatening manifestations of nature, the paper provides an overview of hazard risks and resilience, from an institutional perspective, underlying the main characteristics and lessons that can be learned by smaller administrative units (cities) from the emergence of some shocks. In recent years, European Union policies have focused on the component of (smart) city resilience to fatidic events, which has led us to further highlight the major elements that should define it, in order to minimize as much as possible the negative effects of hazards.
Keywords: 330; shocks; resilience; institutions; hazard risk management; (smart) city policies